PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) SEBAGAI INSTRUMEN PEMBENTUKAN KARAKTER PESERTA DIDIK DI ERA KURIKULUM MERDEKA - Aisyah Dalimunthe (Yayasan An-Nur Meunara Baro, 2025)
The Merdeka Curriculum positions the Projek Penguatan Profil Pelajar Pancasila (P5) as a strategic instrument for character building through authentic, collaborative, and contextual project-based learning. The purpose of this study is to analyze the role of P5 as a character development instrument and to identify the main challenges in its implementation in educational institutions. This research employs a descriptive qualitative approach through a literature study using data sources such as journals, books, scientific articles, and official Merdeka Curriculum documents. Data were collected using documentation techniques, coded based on substantive themes, and analyzed using content analysis, which included data reduction, data presentation, and drawing conclusions. The findings indicate that P5 is effective in developing the six dimensions of the Pancasila Student Profile through reflective, collaborative, and real-life-relevant learning experiences. However, its implementation still faces several obstacles, such as limited teacher competence in designing value-oriented project learning, suboptimal time management, insufficient supporting facilities, and an underdeveloped culture of collaboration. These barriers affect the depth of value internalization achieved through P5. In conclusion, the success of P5 is strongly influenced by teachers’ pedagogical competence, school management support, and the readiness of the learning ecosystem. Systematic reinforcement of teacher capacity and all school components is required for P5 to function optimally in achieving the goals of the Merdeka Curriculum.